2000
DOI: 10.1097/00005344-200006000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and Endothelial Actions of Inhibitors of Substance P Amidation

Abstract: Formation of mature active neuropeptides such as substance P (SP) from their glycine extended precursors entails alpha-amidation of peptide precursors by the sequential enzymatic action of peptidylglycine alpha-monooxygenase (PAM) and peptidylamidoglycolate lyase (PGL). We reported that these two enzymes that can produce mature active neuropeptides are present in cultured bovine aortic endothelial cells (BAECs). We hypothesize that alpha-amidation of peptides occurs in endothelial cells and that these peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It is has long been assumed that the glycine-extended precursors of bioactive peptides have little or no bioactivity prior to amidation [14]. For example, SP-Gly-induced relaxation of rat aortic strips and stimulation of NO production in bovine endothelial cells is markedly reduced in the presence of inhibitors which prevent conversion of SP-Gly to SP [22, 35]. It is therefore apparent that, at least under our experimental conditions, RAW 264.7 macrophages are unable to amidate exogenous SP-Gly to a degree that would stimulate TNF-α production.…”
Section: Discussionmentioning
confidence: 99%
“…It is has long been assumed that the glycine-extended precursors of bioactive peptides have little or no bioactivity prior to amidation [14]. For example, SP-Gly-induced relaxation of rat aortic strips and stimulation of NO production in bovine endothelial cells is markedly reduced in the presence of inhibitors which prevent conversion of SP-Gly to SP [22, 35]. It is therefore apparent that, at least under our experimental conditions, RAW 264.7 macrophages are unable to amidate exogenous SP-Gly to a degree that would stimulate TNF-α production.…”
Section: Discussionmentioning
confidence: 99%
“…Although C-terminal amidation was thought to be essential for the bioactivity of most peptide hormones, there are an increasing number of examples where a glycine-extended intermediate is also bioactive. Examples include secretin-gly, gastrin releasing peptide (GRP)-gly, glucagon-like peptide (GLP)-1-gly and substance P (Wettergren et al 1998, Abou-Mohamed et al 2000, Oiry et al 2000, Solomon et al 2001. However, these glycine-extended forms either interact with the same receptor type as the amidated form or are converted to the mature form close to the site of action.…”
Section: Introductionmentioning
confidence: 99%
“…At least some of substance P's actions result from its ability to suppress the synthesis and release of catecholamines from the adrenal medulla [589], as well as alterations in ACTH-corticosterone production [590]. It has recently been shown that the final a-amidation step necessary for full activity of substance P can occur directly within endothelial cells and can be released by shear stress [591,592]. This endothelialderived substance P can then evoke vasorelaxation through a nitric oxide-dependent mechanism [591].…”
Section: Biological Actions and Receptor Pharmacologymentioning
confidence: 99%
“…It has recently been shown that the final a-amidation step necessary for full activity of substance P can occur directly within endothelial cells and can be released by shear stress [591,592]. This endothelialderived substance P can then evoke vasorelaxation through a nitric oxide-dependent mechanism [591]. Interestingly, the immediate precursor prior to the a-amidation, substance P-Gly, also possesses a vasorelaxant potency similar to that of the mature peptide [593].…”
Section: Biological Actions and Receptor Pharmacologymentioning
confidence: 99%